AN IN-DEPTH ANALYSIS OF HOW CAR, CREDIT RISK, AND LIQUIDITY AFFECT PROFITABILITY - Hasanuh, Nanu; Sulistiyo, Hari; Sidik, Solihin; Suartini, Sri; Ghani, Erlane K; Chudjuarjeen, Saichol; Manda, Gusganda Suria (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT This study examines the impact of credit risk, liquidity, and capital adequacy level (CAR) on profitability in the Indonesian banking sector while accounting for bank size moderation. The results of a linear regression study of panel data using annual financial report data from banks listed on the Indonesia Stock Exchange (2017-2022) show that although credit risk has an adverse effect and liquidity does not affect profitability, CAR does not significantly affect profitability. While bank size enhances the beneficial moderation of credit risk on profitability, it does not mitigate the impact of CAR and liquidity. Encouragement of Indonesian banks to enhance credit risk management while taking into account extra elements like operational effectiveness and product innovation are some of the practical ramifications. Additionally, these findings offer theoretical advancements in the field of agency. ABSTRAK Penelitian ini menguji dampak risiko kredit, likuiditas, dan tingkat kecukupan modal (CAR) terhadap profitabilitas di sektor perbankan Indonesia dengan memperhitungkan moderasi ukuran bank. Hasil studi regresi linier data panel dengan menggunakan data laporan keuangan tahunan dari bank-bank yang terdaftar di Bursa Efek Indonesia (2017-2022) menunjukkan bahwa meskipun risiko kredit memiliki pengaruh negatif dan likuiditas tidak berpengaruh terhadap profitabilitas, namun CAR tidak berpengaruh secara signifikan terhadap profitabilitas. Meskipun ukuran bank meningkatkan moderasi yang menguntungkan dari risiko kredit terhadap profitabilitas, namun tidak mengurangi dampak CAR dan likuiditas. Dorongan bagi bank-bank di Indonesia untuk meningkatkan manajemen risiko kredit dengan mempertimbangkan elemen-elemen lain seperti efektivitas operasional dan inovasi produk merupakan beberapa konsekuensi praktisnya. Selain itu, temuan ini juga memberikan kemajuan teoritis mengenai keagenan.